UJI POTENSI PROBIOTIK Lactobacillus plantarium SECARA IN-VITRO - Maunatin, Anik; Khanifa, Khanifa (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2012)
Probiotic is a product containing non-pathogenic microbes live, which was given to animals or humans to fix the rate of growth, efficiency, and increase conversion ration of animal or human health by affecting positively the balance of the gut microbes and microbial pathogen control in the digestive tract. In order to potentially lactic acid bacteria as probiotic candidates must pass the test selection among others such as probiotic test resistance to acid pH, the bile salts, against pathogenic bacteria. This experimental research methods for descriptive use that aim to provide information about the probiotic potential Â of Lactobacillus plantarum was isolated from the small intestine Mojosari duck (Anasplathyrinchos) with the tests in vitro i.e. the resistance of Lactobacillus plantarum on the condition of the acidicpH (2, 3, and 4), bile salt concentration of 0.3% (b/v), inhibition of pathogenic bacteria (Escherichia coli, Staphylococcus aureus and Salmonella typhi) The results showed that on pH 2 the number of cells of bacteria that lives was 4.3. 107 CFU/ml, pH 3 was Â 3.8. 109 CFU/ml and pH 4 was 2.7. 1010 CFU/ml, the resistance of Lactobacillus plantarum on bile salt showed the number of cells of bacteria that lives was 1.2. 109 CFU/ml.inhibition of the pathogenic bacteria showed thatLactobacillus plantarumcould inhibited strong on Escherichia coli and Staphylococcus aureus with diameter of zone was 12.7 mm and 13.3 mm but notSalmonellatyphi with diameter of zone was 9.3 mm.